Prevalence of HPV types in HIV‐positive and negative females with normal cervical cytology or dysplasia. Issue 4 (17th February 2023) - Aziz, Hafsa; Sattar, Areej A.; Mahmood, Humera; Fatima, Shazia; Khurshid, Mona; Faheem, Mohammad
Abstract: The burden of HPV varies by country and HIV status. The study aimed to evaluate HPV types prevalent in HIV‐positive females compared with HIV‐negative females in the local population of the federal capital territory in Pakistan. Method: The selected female population consisted of 65 already diagnosed HIV‐positive females and 135 HIV‐negative females. Cervical scrap was collected and analyzed for HPV and cytology. Results: The prevalence of HPV in HIV‐positive patients was 36.9%, higher than HIV‐negative patients (4.4%). 12.30% had cervical cytology interpreted as "LSIL" and 87.69% had cytology interpreted as "NIL." The high‐risk type was detected in 15.39% while 21.54% showed low‐risk HPV types. Among the high‐risk types, HPV18 (6.15%), HPV16 (4.62%), HPV45 (3.07%), HPV33 (1.53%), HPV58 (3.07%), and HPV68 (1.53%) were found. In patients with LSIL, high‐risk HPV accounts for 62.5%. Risk factors, such as age, marital status, educational status, residence, parity, other STDs, and contraceptives, were analyzed to find the correlation with HPV infection Age ≤35 years (OR 1.21, 95% CI, 0.44–3.34), illiterate and incomplete secondary education (OR 1.08, 95% CI, 0.37–3.15), and those reported not to use contraceptives (OR: 1.90; 95% CI: 0.67–5.42) have an association for increased risk of HPV infection. Conclusion: HPV18, HPV16, HPV58, HPV45, HPV68, and HPV33 were identified among high‐risk HPV types. High‐risk HPV was detected in 62.5% of low‐grade squamous intraepithelial lesions. The data is useful for health policymakers to develop a strategy for HPV screening and prophylactic vaccination to prevent cervical cancer. Abstract : Distribution of HPV genotypes in HIV positive and HIV negative patients.